The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.soilbio.2020.107863
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization changes soil microbiome functioning, especially phagotrophic protists

Abstract: This article is made publicly available in the institutional repository of Wageningen University and Research, under the terms of article 25fa of the Dutch Copyright Act, also known as the Amendment Taverne. This has been done with explicit consent by the author.Article 25fa states that the author of a short scientific work funded either wholly or partially by Dutch public funds is entitled to make that work publicly available for no consideration following a reasonable period of time after the work was first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 95 publications
3
41
1
Order By: Relevance
“…The assembly and stability of crop microbiomes are jointly influenced by a wide range of abiotic and biotic factors (Trivedi et al ., 2020). There is an increasing recognition that common agricultural management practices, such as organic and inorganic fertilizations, have significant effects on the dynamics, structure and functions of plant and soil microbiomes over time (Bonanomi et al ., 2018; Schmidt et al ., 2019; Zhao et al ., 2020). Soil protists are known to respond to changes in soil physicochemical conditions such as soil pore size, moisture content, pH and nutrients (Oliverio et al ., 2020; Zhao et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assembly and stability of crop microbiomes are jointly influenced by a wide range of abiotic and biotic factors (Trivedi et al ., 2020). There is an increasing recognition that common agricultural management practices, such as organic and inorganic fertilizations, have significant effects on the dynamics, structure and functions of plant and soil microbiomes over time (Bonanomi et al ., 2018; Schmidt et al ., 2019; Zhao et al ., 2020). Soil protists are known to respond to changes in soil physicochemical conditions such as soil pore size, moisture content, pH and nutrients (Oliverio et al ., 2020; Zhao et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing recognition that common agricultural management practices, such as organic and inorganic fertilizations, have significant effects on the dynamics, structure and functions of plant and soil microbiomes over time (Bonanomi et al ., 2018; Schmidt et al ., 2019; Zhao et al ., 2020). Soil protists are known to respond to changes in soil physicochemical conditions such as soil pore size, moisture content, pH and nutrients (Oliverio et al ., 2020; Zhao et al ., 2020). Application of fertilizers, therefore, would impact the plant‐associated protistan communities through directly modifying soil properties or indirectly altering the communities of bacteria and fungi (Allison et al ., 2007; Álvarez‐Martín et al ., 2016) which can impact protists through the trophic food web interactions (Geisen et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, no increase in (phyto)pathogenic bacteria was evidenced after irrigation with reclaimed water or piggery wastewater. Gu et al (2019) also evidenced a modulation of the spinach microbiome according to the quality of irrigation water. Although they did not find any increase in foodborne pathogens, they evidenced an increase in potential opportunistic (phyto)pathogens.…”
Section: Impact Of Irrigation/water On Microbiomementioning
confidence: 89%
“…However, at the early recovery stage, fire perturbations on the protist community may affect soil nutrient cycling, as protists enhance the microbial loop (i.e., releasing nutrients) and increase plant performance (e.g., plant pathogen protection) (Rosenberg et al, 2009). Protist communities are generally influenced by climatic factors (e.g., annual mean rainfall and temperature) (Oliverio et al, 2020), soil moisture, clay content and nutrient status (Zhao et al, 2019(Zhao et al, , 2020, but appear to be not overly sensitive to soil pH (Fiore-Donno et al, 2019). Our results showed that the effects of soil nutrient status, but not soil pH, on protist communities were reduced during the early stage after fire (Fig.…”
Section: Recovery Of Protist Communities and Their Interactions With Bacterial Communitiesmentioning
confidence: 99%